An Analysis of Prophet Muhammad’s Leadership in Tafsir al-Azhar: A Study of Surah Ali ‘Imran Verse 159 - Desma Ayu Artika; Muhammad Said; Siti Asiah (ALSYS, 2026)
Prophetic leadership offers an ethical framework for addressing contemporary leadership challenges, yet its contextual relevance to Indonesian society requires further scholarly examination. This study aimed to analyze Hamka’s interpretation of Prophet Muhammad’s leadership in Tafsir Al-Azhar, with particular emphasis on Surah Ali ‘Imran verse 159, identify the leadership values reflected in the Prophet’s exemplary conduct, and examine their relevance to leadership in Indonesia. The study employed a literature review method using a contextual thematic exegesis approach. The findings indicate that Surah Ali ‘Imran verse 159 emphasizes gentleness and consultation as fundamental principles of leadership. Gentleness is interpreted as a manifestation of Allah’s mercy that strengthens emotional bonds and softens the hearts of followers, whereas consultation represents an inclusive and participatory principle of decision-making. The analysis further identifies trustworthiness, justice, and exemplary conduct as essential characteristics of Prophet Muhammad’s leadership. These values remain highly relevant to contemporary Indonesian leadership because their implementation can promote inclusive decision-making, social harmony, justice, and public welfare. The study concludes that prophetic leadership provides a normative and practical framework for developing ethical, participatory, and welfare-oriented leadership. This study contributes to Islamic leadership scholarship by contextualizing Hamka’s interpretation and demonstrating the applicability of prophetic leadership values to contemporary governance and social leadership in Indonesia.